LAYANAN SIRKULASI DI PERPUSTAKAAN INSTITUT AGAMA ISLAM NEGERI PONTIANAK - Nurillahi, Dimas; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is a hope of researcher to knows the sirculation service in IAIN Pontianak. The aim of this research is describe how important an optimality of sirculation service. In this research, the researcher using a descriptive method with quality approach. The technique of collecting data is doing by observation, interview and documentation with informan subject such as a library principal, a management employee and the sirculation service. The result of this research can show the sirculation service in IAIN Pontianak library is on processing of optimality, the one of problem the process is unavailable a computer to acces an OPAC. The alternative who given the library is the library user can looking for the book is doing by ask to the librarian. Keywords: Circulation service, College library, IAIN Pontianak